An Empirical Study of Cash Payments - Jeanine Kippers; Erjen van Nierop; Richard Paap; Philip Hans Franses (Tinbergen Institute, 2002)
Anytime an individual makes a cash payment, s/he needs to think about theamount to be paid, the coins and notes which are available, and the amount ofchange. For central banks and retail stores, for example, it is of interest to un-derstand how this individual choice process works. The literature of currency useconcerns primarily theory, in the sense that, given certain assumptions, one can de-rive an optimal denomination range. There is no empirical study which deals withthe actual use of coins and notes, given a specific denomination range. In this paperwe therefore present such a study, which is based on two rather unique data sets.We use descriptive statistics and a sophisticated model, which is designed for thisspecific purpose, to see whether two basic premises of the theories on optimal rangesare valid. In contrast to the widely accepted assumptions, we find that individualsappear not to pay efficiently and that they are also not indifferent to the use of coinsand notes. In other words, some notes and coins are used less often than expectedgiven the payment situation.
Keywords: 330; Zahlungsverkehr; Geldnachfrage; Schätzung; Niederlande